Hubungan antara Pelaksanaan Kerja Praktik dan Kemampuan Kerja Alumni Fakultas Pariwisata UKDLSM - Steven Yones Kawatak; Roosalina Hera Lucia; Oktavianus Wayan Semuel (CV. Ulil Albab Corp, 2024)
Human resource is one of the driving and most important factors in the tourism industry. With the richness and diversity of flora and fauna, cultural, and historical art that Indonesia possesses, it requires qualified human resources as well as experts to manage it. North Sulawesi has become one of the provinces with better human resource development compared to other provinces in Indonesia thanks to the role of the government and local culture that shapes the human character. One of the attempts to shape human resource skills is through the institutions of education, where students are given the opportunity to undertake an internship program to develop their skills as well as to experience working in the real world. The aim of this study is to analyze the impact of internship on the work ability of the alumni of the Faculty of Tourism of the Catholic University of De La Salle Manado. The research method used is the Simple Linear Regression Analysis to find out the relationship between internship and ability to work. A purposive sampling techniques was used by spreading questionnaires to 28 respondents. The results of the research show that internship has a positive impact on alumni's ability to work.